Security analysis of a WLAN network sample in Tunja, Boyacá, Colombia (2015)
This paper presents results of a safety analysis of WLAN networks in the city of Tunja, Boyacá Colombia, it is based on a random sample distributed in all over the City. The study is a research result of the project "diagnosis of technology security, applied to a sample of organizations in the city of Tunja". It was funded by the University of Santo Tomas Sectional Tunja. The information collected and analyzed was obtained through the techniques warchalking and Wardriving, in a meaningful representation of wireless networks from public, private, educational institutions and households located geographically in different parts of the city. As a result of the research it was demonstrated different risk levels regarding certain technology configurations of devices of the public, private and residential sectors, finally some conclusions and recommendations were made to enhance the level of security through good practice to configurational level and use of these networks.